Correction to: Associations of sphingosine‑1‑phosphate with soluble P‑selectin and adverse clinical outcome in patients with cerebral ischemia with and without acetylsalicylic acid treatment - Nils‑Ole Gloyer; Eileen Moritz; Laura Schwieren; Ulrike Meyer; Götz Thomalla; Günter Daum; Tim Magnus; Rainer Böger; Chi‑un Choe; Bernhard H. Rauch; Edzard Schwedhelm (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Associations of sphingosine-1-phosphate with soluble P-selectin and adverse clinical outcome in patients with cerebral ischemia with and without acetylsalicylic acid treatment - Nils-Ole Gloyer; Eileen Moritz; Laura Schwieren; Ulrike Meyer; Götz Thomalla; Günter Daum; Tim Magnus; Rainer Böger; Chi-un Choe; Bernhard H. Rauch; Edzard Schwedhelm (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Patients with overt cerebral ischemia are at risk for adverse events after hospital discharge. Sphingosine-1-phosphate is a potent lipid mediator produced and secreted by platelets, which is inhibited via acetylsalicylic acid (ASA). The associations of sphingosine-1-phosphate with biomarkers of platelet activation, i.e., thromboxane B 2 and soluble P-selectin, as well as with clinical outcome in ischemic stroke or transient ischemic attack patients’ subgroups with and without ASA has not yet been investigated. The bioMARKers in STROKE (MARK-STROKE) cohort is a prospective, single-center, observational study including adult patients with a diagnosis of ischemic stroke or transient ischemic attack. Sphingosine-1-phosphate, thromboxane B 2 , and soluble P-selectin were measured by liquid chromatography-tandem mass spectrometry and ELISA, respectively, to investigate cross-sectional and outcome associations in ASA medication groups. Overall, we included 374 patients (median age 70 (IQR 58; 78) years; sex 242 (64.7%) males; ASA, yes 270 (72.2%)). During the first 365 days of follow-up, we recorded 79 adverse events (death, stroke, myocardial infarction, rehospitalization) in 274 patients with available follow-up. While no statistical differences in neurological and functional deficits were determined by sphingosine-1-phosphate, thromboxane B 2 , and soluble P-selectin in both ASA medication groups, patients without ASA intake and high soluble P-selectin had shorter event-free survival times (high soluble P-selectin 250 (95%CI 205; 296) days; low soluble P-selectin 331 (95%CI 304; 358) days; p = 0.005). In addition, adjusted Cox-regression analysis revealed a higher hazard ratio (HR) for an adverse event during follow-up (HR = 3.22 (95%CI 1.41; 7.36); p = 0.005). Our findings may indicate the usability of soluble P-selectin in ASA-naive patients with ischemic stroke/transient ischemic attack for risk stratification.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Epigenetic age deceleration reflects exercise-induced cardiorespiratory fitness improvements - Menno Van Damme; Sanne Stegen; Bram Steenwinckel; Helene Schroé; Gustavo A. Reyes del Paso; Matias M. Pulopulos; Rudi De Raedt; Marie-Anne Vanderhasselt; Wim Derave; Femke Ongenae; Jan Boone; Wim Van Criekinge; et al. (GeroScience, 2026)

On the vertical variability of turbulent heat fluxes within and above a deciduous forest - Temple R. Lee; Sandip Pal; Praveena Krishnan; Tim B. Wilson; Rick D. Saylor; Tilden P. Meyers; John Kochendorfer; Will Pendergrass; Randy White; Mark Heuer (Agricultural and Forest Meteorology, 2025)

Evidence at play: evidence-based practices and barriers in biological maturation assessment among German football academies - Lukas Arenas; Sabrina Skorski; Tim Meyer; Monika Frenger (German Journal of Exercise and Sport Research, 2025)
Purpose This study examined the extent to which German male football academies adopt evidence-based practices (EBP) and their impact on the execution of biological maturation assessments. It also explored perceived barriers to implementing these assessments. Methods With a 71.4% completion rate, 40 support staff members from German male football academies completed an online survey. The survey included questions on clubs’ beliefs about EBP, maturation assessment and monitoring practices, and data utilization. Responses were structured as multiple-choice or unipolar Likert scale questions with four to five labeled points. A magnitude-based decision approach was used to interpret findings. Results Results indicate a strong integration of EBP within German football academies, reflected in an EBP index of 3.66 ± 0.89 on a 5-point Likert scale. Significant differences ( p = 0.035) were observed between participants conducting biological maturation assessments (3.91 ± 0.65) and those who do not (3.44 ± 0.71). Time constraints (68%) and staffing limitations were identified as primary barriers. Conclusion The findings emphasize the positive adoption of evidence-based practices in German football academies, with higher EBP index scores linked to conducting biological maturation assessments. The higher EBP index scores among those conducting biological maturation assessments highlight the crucial role of organizational culture in implementation. Structural barriers, contributing to the perceived “time constraints”, are key challenges, while staff competence is not a limiting factor. Promoting innovative, solution-oriented practices could help address these barriers, enhance decision-making, and better align processes with long-term player development goals.

Nutritional support in professional German football clubs and youth academies—a descriptive study - Dolores Reyzis; Hans Braun; Thomas Hauser; Tim Meyer (German Journal of Exercise and Sport Research, 2025)
Proper nutrition is considered important for the maintenance of health and performance in football players. The more demanding the match and training schedule, the higher the requirements for nutritional advice are. Still, the amount and level of nutritional support is unknown in many (semi-)professional settings. Therefore, the goal of this study was to provide an overview of nutrition practices in clubs of the highest German football leagues and their youth academies. An online survey about nutritional support was distributed to 97 professional male (Bundesliga, 2nd Bundesliga, and 3rd division), female (Women’s Bundesliga), and academy club representatives of which 52 (54% response rate) replied. We found that ~83% ( n = 43) of clubs provide some nutritional advice, mostly for the professional male (69%, n = 35) and academy teams (65%, n = 34), while only 32% ( n = 12) of professional female teams receive support. Nutritional advice is primarily provided by either full-time coaches (27%) or external nutritionists (27%). In about 60% of elite German clubs, daily nutrition offers include one whole meal, sports foods and micronutrient supplementation. Clubs’ representatives (75%) concur that nutrition significantly impacts football performance. Challenges in the implementation of advice are seen in professional players being often quite resistant to advice and in the topic still being “very coach-dependent”. In conclusion, nutrition is regarded an important topic within surveyed clubs, but consistent support by nutrition professionals is sparse, especially for female players. To enhance the quality of nutritional support, professional clubs and academies might consider employing a full-time qualified nutritionist or dietitian.

Eighteen years of daily PM2.5 predictions (2005–2022) for a region of western Canada: Machine learning and satellite inputs for applications in rural health - Miranda Doris; Amira Aker; Élyse Caron-Beaudoin; Coreen Daley; Meredith Franklin; M.G.M. Milani; Margaret J. McGregor; Jannie Leung; Laura Minet; Ulrike Meyer; Lisa A. Ronald; Tim K. Takaro; et al. (Atmospheric Environment, 2025)

Independent Genetic Mapping Experiments Identify Diverse Molecular Determinants of Host Adaptation in a Generalist Herbivore - Ernesto Villacis‐Perez; Femke De Graeve; Berdien De Beer; Seham Ali Alshami; Rick De Jong; Tim De Meyer; Thomas Van Leeuwen (Molecular Ecology, 2025)
Interactions between plants and herbivores promote evolutionary change. Studying the evolution of herbivore mechanisms aimed to cope with different host plant species is a critical intersection between evolutionary biology and sustainable pest management. Generalist herbivores are of particular interest, as hybridization between genetically distinct populations can increase the standing genetic variation and therefore the adaptive potential of the species. Tetranychus urticae is a generalist arthropod known for its adaptive potential, evidenced in its immense host range and ability to develop metabolic resistance to xenobiotics. However, the molecular underpinnings associated with the potential of host adaptation and the consequences of host adaptation in this, and many other pests remain elusive. Here, we use two independent, empirical approaches to identify and map the genetic basis of host plant performance and adaptation in genetically distinct populations of T. urticae . In the first approach, we subject a genetically diverse mite population to tomato selection and map genomic regions linked to the phenotypic evolution of increased reproductive performance. In the second approach, we map genomic regions responsible for performance on tomato by comparing the genomes of pooled individuals from an F2 backcross between populations with high and low reproductive performance. Both approaches revealed specific and shared genomic regions associated with host plant performance and adaptation and key candidate genes were identified. Our findings highlight the power of spider mite genetic approaches to identify the complex genetic basis of host adaptation in generalist herbivores.

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

On the application of the hockey-stick transition hypothesis to characterize turbulence within and above a deciduous forest - Temple R. Lee; Sandip Pal; Praveena Krishnan; Tim B. Wilson; Rick D. Saylor; Tilden P. Meyers; John Kochendorfer; Will Pendergrass; Randy White; Mark Heuer (Agricultural and Forest Meteorology, 2025)

Response to: methodological considerations for assessing SmO2 reproducibility and its applications in sport sciences - Philip Skotzke; Sascha Schwindling; Tim Meyer (European Journal of Applied Physiology, 2025)

Side differences and reproducibility of the Moxy muscle oximeter during cycling in trained men - Philip Skotzke; Sascha Schwindling; Tim Meyer (European Journal of Applied Physiology, 2024)
Purpose Portable near-infrared spectroscopy devices allow measurements of muscle oxygen saturation (SmO 2 ) in real time and non-invasively. To use NIRS for typical applications including intensity control and load monitoring, the day-to-day variability needs to be known to interpret changes confidently. This study investigates the absolute and relative test–retest reliability of the Moxy Monitor and investigates side differences of SmO 2 at the vastus lateralis muscle of both legs in cyclists. Methods Twelve trained cyclists and triathletes completed 3 incremental step tests with 5 min step duration starting at 1.0 W/kg with an increase of 0.5 W/kg separated by 2–7 days. SmO 2 was averaged over the last minute of each stage. For all power outputs, the intra-class coefficient (ICC), the standard error of measurement (SEM) and the minimal detectable change (MDC) were calculated. Dominant and non-dominant leg SmO 2 were compared using a three-factor ANOVA and limits of agreement (LoA). Results ANOVA showed no significant systematic differences between trials and side. For both legs and all intensities, the ICC ranged from 0.79 to 0.92, the SEM from 5 to 9% SmO 2 and the MDC from 14 to 18% SmO 2 . The bias and LoA between both legs were −2.0% ± 19.9% SmO 2 . Conclusion Relative reliability of SmO 2 was numerically good to excellent according to current standards. However, it depends on the specific analytical goal whether the test–retest reliability is deemed sufficient. Wide LoA indicate side differences in muscle oxygenation during exercise unexplained by leg dominance.

Understanding information needs for seamless intermodal transportation: Evidence from Germany - Tim Meyer-Hollatz; Matthias Kaiser; Robert Keller; Marcus Schober (Transportation Research Part D: Transport and Environment, 2024)

Towards reusable building blocks for agent-based modelling and theory development - Uta Berger; Andrew Bell; C. Michael Barton; Emile Chappin; Gunnar Dreßler; Tatiana Filatova; Thibault Fronville; Allen Lee; Emiel van Loon; Iris Lorscheid; Matthias Meyer; Birgit Müller; et al. (Environmental Modelling & Software, 2024)

Microcomputed tomographic analysis of the ulnar trochlear notch in medium- and large-breed canine cadavers with and without medial coronoid disease - Tim Glück; Yury Zablotski; Andrea Meyer-Lindenberg (Research in Veterinary Science, 2024)

Where should hydrology go? An early-career perspective on the next IAHS Scientific Decade: 2023–2032 - Theresa C. van Hateren; Harro J. Jongen; Hadeel Al-Zawaidah; Joris G.W. Beemster; Judith Boekee; Linda Bogerd; Sijia Gao; Christin Kannen; Ilja van Meerveld; Sjoukje I. de Lange; Felicia Linke; Rose B. Pinto; et al. (Hydrological Sciences Journal, 2023)

Provenance of Oligocene–Miocene sedimentary rocks in the Cuu Long and Nam Con Son basins, Vietnam and early history of the Mekong River - H. Tim Breitfeld; Juliane Hennig-Breitfeld; Marcelle BouDagher-Fadel; William J. Schmidt; Kevin Meyer; Jeff Reinprecht; Terrence Lukie; Trinh Xuan Cuong; Robert Hall; Nils Kollert; Amy Gough; Rafika Ismail (International Journal of Earth Sciences, 2022)
The offshore Cuu Long (CLB) and Nam Con Son (NCSB) basins of SE Vietnam are two important Cenozoic hydrocarbon-bearing basins in the southern South China Sea (SCS), which can contribute to understanding the evolution of major SE Asian river systems, in particular the Mekong River. The Oligocene to Early Miocene basin fill of the Cuu Long Basin is dominated by sediment sourced locally from the Da Lat Zone basement on land. Sandstones have abundant Cretaceous detrital zircons and heavy mineral assemblages dominated by apatite and epidote. The Bach Ho Unconformity at c. 16 to 20.5 Ma marks a major provenance change and the overlying Middle to Late Miocene Con Son and Dong Nai formations were sourced by a large river system, which drained Indochina or even the Himalaya, resembling the present-day Mekong River. These formations have heterogeneous detrital zircon populations dominated by Triassic ages and zircon–rutile–tourmaline-dominated heavy mineral assemblages. The Oligocene Cau and Early Miocene Dua formations of the Nam Con Son Basin have a similar provenance to the CLB Con Son and Dong Nai formations, indicating a comparable drainage history of a large proto-Chao Phraya. At the Dua Unconformity at c. 15.4 to 17 Ma the Indochina provenance signature changes to a predominant Sibumasu signature. The early Mekong River evolution is suggested to have involved two river systems. A proto-Mekong 1 initially filled the CLB, while at the same time a proto-Chao Phraya River with a capture area into the Himalaya filled the Malay Basin and/or the NCSB. At the end of the Early Miocene drainage was completely reorganised, and the proto-Mekong 1 captured the headwaters of the proto-Chao Phraya and became the proto-Mekong 2, while the NCSB was filled by sediment from the Malay–Thai Peninsula. This major change marks a very important drainage reorganisation in the southern SCS region.

Reduction of deoxynivalenol, T-2 and HT-2 toxins and associated Fusarium species during commercial and laboratory de-hulling of milling oats - Jens C. Meyer; Tim Birr; Inga Hennies; Detlev Wessels; Karin Schwarz (Food Additives & Contaminants: Part A, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Haematological and metabolic profiles associated with age and sex in giant kokopu ( Galaxias argenteus ) ( Gmelin 1789) broodstock - Ronald Lulijwa; Andrea C. Alfaro; Leonie Venter; Tim Young; Paul Decker; Fabrice Merien; Jill Meyer (Journal of Fish Biology, 2021)
This study characterized selected peripheral blood (PB) haematological parameters, liver, serum and muscle metabolic features in 3‐ and 5‐year‐old male and female giant kokopu ( Galaxias argenteus ) broodstock reared indoor at 16°C. Sex and age did not affect PB total cell count and haematocrit values. Nonetheless, higher erythrocytes in 5‐year‐old fish, elevated thrombocyte and lymphocyte counts in 3‐year‐old fish indicate age‐specific cellular regulation. Higher thrombocyte counts in female fish suggest sex‐specific regulation. At a metabolic level, liver abundance for long chain saturated fatty acids (FAs) was higher in males, whereas females had elevated levels of polyunsaturated FAs. Essential and non‐essential amino acids (AAs) in liver and serum were also elevated in females compared to males. These findings suggest differential allocation of FAs and AAs to reflect requirements for gonadal, development and provisioning. Similarly, age significantly resulted in higher liver and serum abundances of some non‐essential AAs in 3‐year‐olds compared to 5‐year‐old fish, suggesting higher metabolism in younger fish. Overall, results enhance our understanding of sex‐ and age‐based differences in fish haematology, muscle, liver, and serum metabolite profiles in healthy G. argenteus . Future studies should carefully consider potential age‐ and sex‐specific differences in metabolic responses.

Effect of anticoagulants on farmed giant kokopu, Galaxias argenteus (Gmelin 1789) haematological parameters and erythrocyte fragility - Ronald Lulijwa; Andrea C. Alfaro; Tim Young; Leonie Venter; Paul Decker; Fabrice Merien; Jill Meyer (Journal of Fish Biology, 2021)
We sought to determine a compatible anticoagulant for routine haematological and physiological assessments with giant kokopu ( Galaxias argenteus ), an endemic New Zealand fish. We observed that blood treated with lithium heparin (LH) rapidly coagulated and haemolysed, making it unsuitable for G. argenteus . Dipotassium ethylenediaminetetraacetic acid (K 2 EDTA) and trisodium citrate (citrate) effectively prevented blood coagulation. K 2 EDTA‐treated erythrocytes exhibited the least mean haemolysis and mean corpuscular fragility. Further studies into prolonged storage effects of citrate and K 2 EDTA are recommended to find a compatible anticoagulant for use with G. argenteus blood.

Long‐term development and trajectories of inferred lake‐water organic carbon and pH in naturally acidic boreal lakes - Erik Myrstener; Sofia Ninnes; Carsten Meyer‐Jacob; Tim Mighall; Richard Bindler (Limnology and Oceanography, 2021)
Monitoring of surface waters in the boreal region over the last decades shows that waters are becoming browner. This timeframe may not, however, be sufficient to capture underlying trajectories and driving mechanisms of lake‐water quality, important for prediction of future trajectories. Here we synthesize data from seven lakes in the Swedish boreal landscape, with contemporary lake‐water total organic carbon (TOC) concentrations of 1.4–14.4 mg L −1 , to conceptualize how natural and particularly human‐driven processes at the landscape scale have regulated lake‐water TOC levels over the Holocene. Sediment‐inferred trends in TOC are supported by several proxies, including diatom‐inferred pH. Before ~ 700 ce , all lakes were naturally acidic (pH 4.7–5.4) and the concentrations of inferred lake‐water TOC were high (10–23 mg L −1 ). The introduction of traditional human land use from ~ 700 ce led to a decrease in lake‐water TOC in all lakes (to 5–14 mg L −1 ), and in four poorly buffered lakes, also to an increase in pH by > 1 unit. During the 20 th century, industrial acid deposition was superimposed on centuries of land use, which resulted in unprecedentedly low lake‐water TOC in all lakes (3–11 mg L −1 ) and severely reduced pH in the four poorly buffered lakes. The other lakes resisted pH changes, likely due to close connections to peatlands. Our results indicate that an important part of the recent browning of boreal lakes is a recovery from human impacts. Furthermore, on a conceptual level we stress that contemporary environmental changes occur within the context of past, long‐term disturbances.

Assessment of sleep quality and daytime sleepiness in German national ice hockey players preparing for the world championship - Annika Hof zum Berge; Fabian Loch; Karl Schwarzenbrunner; Alexander Ferrauti; Tim Meyer; Mark Pfeiffer; Michael Kellmann (German Journal of Exercise and Sport Research, 2021)
Objectives Objectives were to examine subjective sleep quality and daytime sleepiness of the German ice hockey junior national team prior to the world championship to identify athletes of concern and areas of optimization with the intention of equally preventing injury and enhancing performance. Methods Twenty-one athletes ( M age = 18.5 ± 0.6 years, M height = 181.7 ± 4.3 cm, M weight = 81.4 ± 7.1 kg), playing for national ( n = 13) and international ( n = 8) home clubs, answered the Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS) before training camp (T1, day 1) and prior to tournament (T2, day 11). Results Overall, 9 players at T1 and 7 at T2 were identified as bad sleepers (PSQI > 5), while high sleepiness (ESS > 10) was found for 6 athletes at each measurement time. Group means and standard deviations reduced descriptively for PSQI (T1 = 5.38 ± 2.31, T2 = 4.57 ± 2.36) and ESS (T1 = 9.24 ± 3.74, T2 = 8.48 ± 3.28). Tendential differences were visible for PSQI in international-based players (Z = −1.7, p = 0.09) and ESS in first-national-league players (Z = −1.73, p = 0.08) over time. Higher PSQI values for international-based players (6.25 ± 2.6) were found compared to first-national-league (5.83 ± 1.60) and lower-league players (4.00 ± 2.08), with large effect sizes for lower-league compared to international ( d = 0.95) and national players ( d = 0.98) at T1 and small effect sizes compared to first-league players ( d = 0.24) at T2. Conclusion Findings emphasize great vulnerability and individuality and underline the importance of intraindividual sleep monitoring to meet the requirements needed to equally obtain health and enhance overall performance.

Extreme Levels of Ocean Acidification Restructure the Plankton Community and Biogeochemistry of a Temperate Coastal Ecosystem: A Mesocosm Study - Carsten Spisla; Jan Taucher; Lennart T. Bach; Mathias Haunost; Tim Boxhammer; Andrew L. King; Bettany D. Jenkins; Joselynn R. Wallace; Andrea Ludwig; Jana Meyer; Paul Stange; Fabrizio Minutolo; et al. (Frontiers in Marine Science, 2021)
The oceans’ uptake of anthropogenic carbon dioxide (CO 2 ) decreases seawater pH and alters the inorganic carbon speciation – summarized in the term ocean acidification (OA). Already today, coastal regions experience episodic pH events during which surface layer pH drops below values projected for the surface ocean at the end of the century. Future OA is expected to further enhance the intensity of these coastal extreme pH events. To evaluate the influence of such episodic OA events in coastal regions, we deployed eight pelagic mesocosms for 53 days in Raunefjord, Norway, and enclosed 56–61 m 3 of local seawater containing a natural plankton community under nutrient limited post-bloom conditions. Four mesocosms were enriched with CO 2 to simulate extreme p CO 2 levels of 1978 – 2069 μatm while the other four served as untreated controls. Here, we present results from multivariate analyses on OA-induced changes in the phyto-, micro-, and mesozooplankton community structure. Pronounced differences in the plankton community emerged early in the experiment, and were amplified by enhanced top-down control throughout the study period. The plankton groups responding most profoundly to high CO 2 conditions were cyanobacteria (negative), chlorophyceae (negative), auto- and heterotrophic microzooplankton (negative), and a variety of mesozooplanktonic taxa, including copepoda (mixed), appendicularia (positive), hydrozoa (positive), fish larvae (positive), and gastropoda (negative). The restructuring of the community coincided with significant changes in the concentration and elemental stoichiometry of particulate organic matter. Results imply that extreme CO 2 events can lead to a substantial reorganization of the planktonic food web, affecting multiple trophic levels from phytoplankton to primary and secondary consumers.

Leserbrief zu Thieme, L. Jung stirbt, wen die Götter lieben? Ger J Exerc Sport Res 50, 280–296 (2020). https://doi.org/10.1007/s12662-020-00654-x - Wilhelm Bloch; Anja Hirschmüller; Frank Mayer; Andreas Nieß; Tim Meyer; Claus Reinsberger; Kai Röcker; Jürgen M. Steinacker (German Journal of Exercise and Sport Research, 2020)

Polyinosinic:polycytidylic acid in vivo enhances Chinook salmon (Oncorhynchus tshawytscha) immunity and alters the fish metabolome - Ronald Lulijwa; Andrea C. Alfaro; Fabrice Merien; Mark Burdass; Jill Meyer; Leonie Venter; Tim Young (Aquaculture International, 2020)

EVI1 oncoprotein expression and CtBP1-association oscillate through the cell cycle - Roberto Paredes; Marion Schneider; Stella Pearson; Hsiang Yin Teng; James R. Kelly; Andrew Pierce; Tim C. P. Somervaille; Anthony D. Whetton; Stefan Meyer (Molecular Biology Reports, 2020)
Aberrantly high expression of EVI1 in acute myeloid leukaemia (AML) is associated with poor prognosis. For targeted treatment of EVI1 overexpressing AML a more detailed understanding of aspects of spatiotemporal interaction dynamics of the EVI1 protein is important. EVI1 overexpressing SB1690CB AML cells were used for quantification and protein interaction studies of EVI1 and ΔEVI1. Cells were cell cycle-synchronised by mimosine and nocodazole treatment and expression of EVI1 and related proteins assessed by western blot, immunoprecipitation and immunofluorescence. EVI1 protein levels oscillate through the cell cycle, and EVI1 is degraded partly by the proteasome complex. Both EVI1 and ΔEVI1 interact with the co-repressor CtBP1 but dissociate from CtBP1 complexes during mitosis. Furthermore, a large fraction of EVI1, but not ΔEVI1 or CtBP1, resides in the nuclear matrix. In conclusion, EVI1- protein levels and EVI1-CtBP1 interaction dynamics vary though the cell cycle and differ between EVI1 and ΔEVI1. These data ad to the functional characterisation of the EVI1 protein in AML and will be important for the development of targeted therapeutic approaches for EVI1-driven AML.

Atmospheric moisture pathways of East Africa and implications for water recycling at Mount Kilimanjaro - Benjamin Schumacher; Marwan Katurji; Hanna Meyer; Tim Appelhans; Insa Otte; Thomas Nauss (International Journal of Climatology, 2020)
The Mt. Kilimanjaro ecosystem depends on atmospheric moisture transport and recycling of water, yet limited knowledge on the relation between advective moisture pathways and local water recycling is available. This study uses a regional atmospheric model to analyse moisture source and sink processes as well as precipitation recycling at Mt. Kilimanjaro. The results indicate that locally produced precipitation is deposited mainly in June and July while trans‐regional effects are weak. Results also revealed the importance of tropical storm systems for local convection in the Kilimanjaro region and the effect of the Indian Ocean Zonal Mode phases on East African moisture pathways. The analysis further revealed connections between the Madagascar tip jet and the Turkana jet with implications for regional moisture pathways that have not been described before.

Metabolic and immune responses of Chinook salmon ( Oncorhynchus tshawytscha ) smolts to a short‐term poly (I:C) challenge - Ronald Lulijwa; Andrea C. Alfaro; Fabrice Merien; Mark Burdass; Jill Meyer; Leonie Venter; Tim Young (Journal of Fish Biology, 2020)
Polyinosinic:polycytidylic acid [poly (I:C)] was administered in vivo to Chinook salmon ( Oncorhynchus tshawytscha ) post‐smolts to determine the immune responses on haematological and cellular functional parameters, including spleen (SP), head kidney (HK) and red blood cell (RBC) cytokine expression, as well as serum metabolomics. Poly (I:C) in vivo (24 h exposure) did not affect fish haematological parameters, leucocyte phagocytic activity and phagocytic index, reactive oxygen species and nitric oxide production. Gas chromatography–mass spectrometry–based metabolomics revealed that poly (I:C) significantly altered the serum biochemistry profile of 25 metabolites. Metabolites involved in the branched‐chain amino acid/glutathione and transsulphuration pathways and phospholipid metabolism accumulated in poly (I:C)–treated fish, whereas those involved in the glycolytic and energy metabolism pathways were downregulated. At cytokine transcript level, poly (I:C) induced a significant upregulation of antiviral ifnγ in HK and Mx1 protein in HK, SP and RBCs. This study provides evidence for poly (I:C)–induced, immune‐related biomarkers at metabolic and molecular levels in farmed O. tshawytscha in vivo . These findings provide insights into short‐term effects of poly (I:C) at haematological, innate and adaptive immunity and metabolic levels, setting the stage for future studies.

Selection of miRNA reference genes for plant defence studies in rice (Oryza sativa) - Bruno Verstraeten; Lien De Smet; Tina Kyndt; Tim De Meyer (Planta, 2019)

Ground Data are Essential for Biomass Remote Sensing Missions - Jérôme Chave; Stuart J. Davies; Oliver L. Phillips; Simon L. Lewis; Plinio Sist; Dmitry Schepaschenko; John Armston; Tim R. Baker; David Coomes; Mathias Disney; Laura Duncanson; Bruno Hérault; et al. (Surveys in Geophysics, 2019)

Speciation and accumulation of Zn in sweetcorn kernels for genetic and agronomic biofortification programs - Zhong Xiang Cheah; Peter M. Kopittke; Stephen M. Harper; Gregor Meyer; Tim J. O’Hare; Michael J. Bell (Planta, 2019)

Efficacy of novel selective NLRP3 inhibitors in human and murine retinal pigment epithelial cells - Luping Wang; Sarah Schmidt; Petra P. Larsen; Johanna H. Meyer; William R. Roush; Eicke Latz; Frank G. Holz; Tim U. Krohne (Journal of Molecular Medicine, 2019)

Sozialer Status und Spendenverhalten Ehrenamtlicher in Sportvereinen - Eike Emrich; Martin Hämmerle; Christoph Behrens; Tim Meyer; Christian Pierdzioch (German Journal of Exercise and Sport Research, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Influence of Ocean Acidification and Deep Water Upwelling on Oligotrophic Plankton Communities in the Subtropical North Atlantic: Insights from an In situ Mesocosm Study - Jan Taucher; Lennart T. Bach; Tim Boxhammer; Alice Nauendorf; Eric P. Achterberg; María Algueró-Muñiz; Javier Arístegui; Jan Czerny; Mario Esposito; Wanchun Guan; Mathias Haunost; Henriette G. Horn; et al. (Frontiers in Marine Science, 2017)

Statistical modeling of a larval mosquito population distribution and abundance in residential Brisbane - Daniel K. Heersink; Jacqui Meyers; Peter Caley; Guy Barnett; Brendan Trewin; Tim Hurst; Cassie Jansen (Journal of Pest Science, 2016)

Protocols for staining of bile canalicular and sinusoidal networks of human, mouse and pig livers, three-dimensional reconstruction and quantification of tissue microarchitecture by image processing and analysis - Seddik Hammad; Stefan Hoehme; Adrian Friebel; Iris von Recklinghausen; Amnah Othman; Brigitte Begher-Tibbe; Raymond Reif; Patricio Godoy; Tim Johann; Amruta Vartak; Klaus Golka; Petru O. Bucur; et al. (Archives of Toxicology, 2014)

Rapid genetic adaptation precedes the spread of an exotic plant species - Katrien Vandepitte; Tim de Meyer; Kenny Helsen; Kasper van Acker; Isabel Roldán‐Ruiz; Joachim Mergeay; Olivier Honnay (Molecular Ecology, 2014)
Human activities have increasingly introduced plant species far outside their native ranges under environmental conditions that can strongly differ from those originally met. Therefore, before spreading, and potentially causing ecological and economical damage, non‐native species may rapidly evolve. Evidence of genetically based adaptation during the process of becoming invasive is very scant, however, which is due to the lack of knowledge regarding the historical genetic makeup of the introduced populations and the lack of genomic resources. Capitalizing on the availability of old non‐native herbarium specimens, we examined frequency shifts in genic SNP s of the P yrenean R ocket ( S isymbrium austriacum subsp. chrysanthum ), comparing the (i) native, (ii) currently spreading non‐native and (iii) historically introduced gene pool. Results show strong divergence in flowering time genes during the establishment phase, indicating that rapid genetic adaptation preceded the spread of this species and possibly assisted in overcoming environmental constraints.

Observations on the entomopathogenic fungus Hirsutella citriformis attacking adult Diaphorina citri (Hemiptera: Psyllidae) in a managed citrus grove - David G. Hall; Matthew G. Hentz; Jason M. Meyer; Alissa B. Kriss; Tim R. Gottwald; Drion G. Boucias (BioControl, 2012)

Patterns of sex ratio variation and genetic diversity in the dioecious forest perennial Mercurialis perennis - Katrien Vandepitte; Olivier Honnay; Tim De Meyer; Hans Jacquemyn; Isabel Roldán-Ruiz (Plant Ecology, 2010)

Physiological characteristics of badminton match play - Oliver Faude; Tim Meyer; Friederike Rosenberger; Markus Fries; Günther Huber; Wilfried Kindermann (European Journal of Applied Physiology, 2007)

Effect of aerobic exercise on behavioral and neuroendocrine responses to meta-chlorophenylpiperazine and to ipsapirone in untrained healthy subjects - Andreas Broocks; Tim Meyer; Gleiter C.; Ursula Hillmer-Vogel; Annette George; Uwe Bartmann; Borwin Bandelow (Psychopharmacology, 2001)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)